Case Report: Autosomal dominant polycystic kidney disease and Wilms’ tumor in infancy and childhood - Zina, Doviltyte; Rosita, Kiudeliene; Kristina, Zviniene; Giedre, Rutkauskiene; Jurate, Masalskiene (Frontiers in Pediatrics, 2024)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is rare but one of the most common inherited kidney diseases. Normal kidney function is maintained until adulthood in most patients. About 7 in 10 patients with ADPKD develop kidney failure in the latter half of their fifth decade of life. Wilms’ tumor, or nephroblastoma, is the most common malignant tumor stemming from kidney cells in the pediatric age group. This type of tumor is the most frequently occurring kidney malignancy in children between the ages of 0 and 5 years. The exact cause of Wilms’ tumor is unknown, though about 10% of cases have a genetic predisposition. Wilms’ tumor is one of the most successfully treated childhood oncological diseases. Overall, the 5-year survival rates were approximately 90% in both the National Wilms Tumor Study (NWTS) and Paediatric Oncology SIOP studies, showing similar results. Case presentation: We report a case of a girl diagnosed with autosomal polycystic kidney disease, who subsequently developed Wilms’ tumor and underwent successful treatment with chemotherapy. Polycystic kidney disease was suspected in the fetus during prenatal ultrasound and confirmed after birth with ultrasound and genetic testing. The Wilms tumor was an accidental finding during abdominal MRI at the age of 2 years old to rule out liver pathology. Conclusion: Reports on whether a diagnosis of ADPKD is a risk factor for malignancy are conflicting. In this particular case, Wilms’ tumor is present in the background of polycystic kidney disease and was timely diagnosed by an incidental MRI.